An admissible estimator for the rth power of a bounded scale parameter in a subclass of the exponential family under entropy loss function - Alikhani, S.; Mahmoudi, E.; Torabi, H. (Український математичний журнал, 2012)
We consider an admissible estimator for the rth power of a scale parameter that is lower or upper bounded in a subclass of the scale-parameter exponential family under the entropy loss function. An admissible estimator for a bounded parameter in the family of transformed chi-square distributions is also given. Розглянуто допустиму оцiнку для r-го степеня параметра масштабу, обмеженого зверху або знизу у пiдкласi експоненцiальної сiм’ї параметрiв масштабу з ентропiйною функцiєю втрат. Наведено також допустиму оцiнку обмеженого параметра у сiм’ї трансформованих розподiлiв хi-квадрат.